2014
DOI: 10.1136/bjsports-2014-093494.33
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Whole-Body Cryostimulation to Improve the Quality of Sleep in Athletes During High Level Standard Competitions

Abstract: BackgroundThis is a field study realized during basketball preparation tournaments for the European championship 2013 with men and women French team. During these competitions, athletes used Whole-Body Cryostimulation (WBC) exposures to enhance their recovery.ObjectiveThe aim of this work was to investigate the effects of WBC on the quality of sleep (QS) in athletes during the night following the exposure.DesignThe preparation took place during one week in a training camp followed by three international matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Whole-body and partial-body cold air cryostimulation (WBC and PBC) are now presented as modern cryotherapy techniques with an ever-growing popularity in the sport and medical sphere (Bleakley et al 2014). The use of WBC is multiple, including post-exercise recovery for athletes (Dupuy et al 2018), pain soothing in inflammatory conditions (Banfi et al 2009;Guillot et al 2014;Dupuy et al 2018) as well as well-being and sleep management (Bouzigon et al 2014;Douzi et al 2019a, b). The physiological and psychological actions of WBC originate from a reduction in skin temperature which triggers a cascade of reactions starting with a peripheral vasoconstriction through sympathetic tuning (Westerlund et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Whole-body and partial-body cold air cryostimulation (WBC and PBC) are now presented as modern cryotherapy techniques with an ever-growing popularity in the sport and medical sphere (Bleakley et al 2014). The use of WBC is multiple, including post-exercise recovery for athletes (Dupuy et al 2018), pain soothing in inflammatory conditions (Banfi et al 2009;Guillot et al 2014;Dupuy et al 2018) as well as well-being and sleep management (Bouzigon et al 2014;Douzi et al 2019a, b). The physiological and psychological actions of WBC originate from a reduction in skin temperature which triggers a cascade of reactions starting with a peripheral vasoconstriction through sympathetic tuning (Westerlund et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle cooling during and after cold exposure may also lower enzyme activities, lower the metabolism and limit protein degradation after exercise-induced ischemia, which can be an important feature for recovery improvement ( Bleakley and Hopkins, 2010 ; Costello et al, 2012 ). Moreover, athletes using PBC during high-level international tournaments seem to have an enhanced quality of sleep ( Bouzigon et al, 2014 ). PBC has therefore been well accepted by many athletes and professional sport teams ( Banfi et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The anti-inflammatory and analgesic effects of WBC are the most searched for by athletes and patients. Recent studies have confirmed these and other beneficial effects of extremely low temperatures in athletes [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 87%